Para uma compreensão da Clausura Monástica e Emparedamento enquanto fenómenos históricos e religiosos - Paula Barata Dias (Medievalista)
The closure, voluntary or involuntary under the ground, in a tomb, a cave or between tight walls, is an ancient practice, crossing various times and places in the history of man, both as punishment, propitiatory sacrifice or funeral ritual. In all these cases, the religious background is present. In this article we seek the relations between the enclosure and the walling in as parts of a universal religious language and we explore the manifestations of self closure and desired walling in which took place in a particular moment of increasing ascetic and monastic mouvements of the history of Christianity. Far from being exhaustive in enumerating concrete cases of closure and walling in, we intent to present reasons for the progressive feminization of this phaenomenon well documented in the medieval world.